Underestimated Survival of Campylobacter in Raw Milk Highlighted by Viability Real-Time PCR and Growth Recovery - Wulsten, Imke F.; Galeev, Alibek; Stingl, Kerstin (Frontiers in Microbiology, 2020)
Raw milk is a frequent vehicle for transmission of thermophilic Campylobacter, leading to reported outbreaks. Milk is a challenging food matrix for pathogen detection, due to its high protein and lipid content. Limited detection of Campylobacter CFU in raw milk might underestimate the pathogen’s infectious potential. We optimized a viability qPCR for application with raw milk. The procedure was robust against variations of milk lots and different Campylobacter strains. Various DNA-intercalating dyes were evaluated for their ability to reduce the PCR signal of dead cells. Only PMA and PMAxx qualified for diagnostic use. Different sedimentation properties of viable and dead C. jejuni and C. coli strains in 10-fold diluted milk enhanced viable/dead differentiation. The new method enabled to review survival of Campylobacter spp. in raw milk based on viable cells harboring an intact cell membrane. The data were compared to culturability according to ISO10272-2:2017. A difference of up to 4.5 log10 between viable Campylobacter counts and CFU values became apparent. Relevance of viability qPCR values was corroborated by full recovery of CFU under extremely reduced oxygen concentration in the presence of hydrogen. Recovery of CFU was limited, however, upon prolonged exposure in raw milk. The data confirm that Campylobacter survival in raw milk can be largely underestimated when relying on CFU data only. We conclude that raw milk led to oxidative stress-induced growth arrest in thermophilic Campylobacter, which was reversible by reduction of the oxygen partial pressure in a time-limited way.